GAMBARAN PERUBAHAN KLINIS DAN RADIOLOGI PASIEN AIDS DENGAN ENSEFALITIS TOKSOPLASMA PASCA TERAPI EMPIRIS - Ahmad Yanuar*, Darma Imran*, Melita**, Joedo Prihartono*** (NEURONA, 2010)
INTRODUCTION IN PATIENTS WITH THE ACQUIRED IMMUNODEFICIENCY SYNDROMEAIDS TOXOPLASMIC ENCEPHALITIS TE IS USUALLY A PRESUMPTIVE DIAGNOSISBASED ON THE CLINICAL MANIFESTATIONS AND A FOCAL LESION ON NEURORADIOLOGIC IMAGING